ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR SARANG BURUNG DI INDONESIA - Harapuspa, Annisa; Fitriani, Dyah (Universitas Ahmad Dahlan, 2018)
Indonesia is a country rich in natural resources and with a wealth of this nature, Indonesian people are able to get care from nature. Indonesia is the largest swallow nest producer in the world, with an average production of 500-600 tons (2011 period). The purpose of this study was to find out the factors of Indonesian bird nest exports to China. SWOT is the analytical method used in this study. Strategic planning methods are used to evaluate strengths, weaknesses, opportunities, and threats in a project or business speculation. A target pattern of structure that is mutually supportive and complementary leads to a comprehensive goal. As preparation for planning, in order to be able to choose and set strategies and objectives so that programs and projects are arranged that are effective and efficient. The results of the analysis using SWOT show that the strategy can be applied by swallow nest breeders in Indonesia is a strategy that uses the power to take advantage of opportunities and instead take advantage of opportunities and make them a force. This strategy uses the company’s internal strength to take advantage of external opportunities. Swallow nest farmers can use the strategy of previous breeders who have exported swallow nest products by fixing some weaknesses and avoiding or surviving against the threat of the company by creating a more competitive strategy.